SCIENTIFIC EVOLUTION AND ACADEMIC TEACHING OF INTELLECTUAL PROPERTY LAW - Ortiz Mora, Guadalupe (2026)
Intellectual property, as well as tangible property, is part of the so-called private property. Both are regulated in the Political Constitution, under articles 47 and 45 respectively. On the occasion of the sixtieth anniversary of the Revista de Ciencias Jurídicas (hereinafter RCJ), which is one of the longest-running law reviews in Costa Rica and Latin America, I would like to refer to several essays that Costa Rican authors have written on this subject since 1988, which reflect the scientific evolution of intellectual property from that date until 2022. Throughout these years, the essays that I will review published in the RCJ have strengthened the adoption, extension and knowledge of Intellectual Property, both from the academic and professional point of view, extensive to the entire legal forum. Emphasis will also be made on national regulations, international agreements that have had relevance in this matter and the incidence of these in the different figures of intellectual property.